Unraveling elements of value-based pricing from a pharmaceutical industry’s perspective: a scoping review - Dane, Aniek; Uyl-de Groot, Carin; van der Kuy, Hugo (Frontiers in Pharmacology, 2024)
Health authorities use value-based pricing models to determine the value of innovative drugs and to establish a price. Pharmaceutical companies prefer value-based pricing over cost-based pricing.It is ambiguous whether value-based pricing has the same meaning to these stakeholders. We aimed to identify the elements that attribute to value-based pricing of innovative drugs from a pharmaceutical industry's perspective and as possible starting point for (value-based) contracting of drugs.We performed a scoping review of publications available in scientific databases with terms such as 'value-based pricing', 'pharmacoeconomics', 'drug cost', 'innovative drug' and 'drug therapy'.We included 31 publications, covering value elements of innovative drugs from a pharmaceutical industry's perspective.Overall, all found elements of value-based pricing were congruent with the elements of valuebased pricing from a health authority's perspective. However, the emphasis placed on the elements differed. The most frequently mentioned elements in our review were economic considerations and cost aspects. Least mentioned were elements regarding cost-effectiveness, disease characteristics and patient characteristics.Although all elements in the drug value framework were present which indicate congruity, there seems controversy on the importance of cost-effectiveness as an element of value. Consequently, establishing a coherent and to all stakeholders' acceptable framework to value and price innovative drugs seems complicated. Mutual understanding can be found in the value elements societal considerations and healthcare process benefits. Our results supported the importance of economic and cost aspects regarding determination of prices of innovative drugs. Further research is required to quantify the weights of all relevant elements in the drug value framework, observe their possible interlinkages, and to weigh them over time.